Assembly of Fe7S8 and Co9S8 nanosheets coupled with Cu(OH)2 nanorods as highly efficient oxygen evolution catalyst. (15th March 2023) - Liu, Weidong; Yang, Shaohua; Lei, Nana; Wang, Limin; Gong, Yaqiong
Abstract: Traditional fossil fuels can be replaced with hydrogen, and electrolysis of water is thought to be one of the most efficient ways to produce hydrogen that is also pollution-free. The oxygen evolution reaction (OER), which is thought to be the bottleneck of the entire water decomposition, is a result of the intricate electrochemical mechanism and the slow kinetic process. In this paper, Cu(OH)2 forerunners with nanorods structure were combined on copper froth by straightforward submersion technique. Then, in a standard three-electrode system Fe7 S8 and Co9 S8 nanosheets with 3D structures were assembled on Cu(OH)2 precursors by electrodeposition. At an alkaline environment of 1 M KOH, Cu(OH)2 /CF requires an overpotential of only 235 mV when the current density reaches 10 mA cm −2, which is lower than that of other reported catalysts. In addition, Fe7 S8 –Co9 S8 @Cu(OH)2 /CF also showed excellent OER performance after long-term stability test, because bimetallic synergism can adjust the electronic structure of the catalyst and optimize its electrical conductivity. A feasible method for the design of a highly efficient oxygen evolution catalyst based on copper foam is reported in this paper. Graphical abstract: The synthesized Fe7 S8 –Co9 S8 @Cu(OH)2 /CF electrode exhibits excellent electrocatalytic performance for OER in 1 M KOH solution. Image 1 Highlights: Fe7 S8 and Co9 S8 nanosheets loaded on Cu(OH)2 nanorods were synthesized on CF. The synthesized sample showed excellent OER catalytic activity in 1 M KOH solution. Nanosheets provide large surface area, and accelerate electron transfer rate.